The Effects of Some Biocontrol Agents and their Combination on Root-knot Disease on Tomato. Issue 1 (2011) - Golzary, Hadi; Ahmadzadeh, Masuod; Panjehkeh, Naser; Salari, Mohammad; Sedaghati-khoravi, Ebrahim
No abstract available